Investigating EFL Students' Speaking Anxiety in Public Speaking Activity at English Department of UNISMA - Pinka Anjela Kusuma Cahyani (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aimed to investigate about level of EFL students speaking anxiety in public speaking activity at English Department of UNISMA and solution of speaking anxiety. This research used descriptive quantitative and qualitative method with purposive sampling techniques. The participants are the fourth-semester students who are joining public speaking class. The researcher used PSCAS questionnaire and interview as the instrument. Thus, the total participating in this questionnaire was 60 students and 5 students were selected to be purposively respondent to join the interview. The result of this study is the fourth-semester students at English Department of UNISMA had moderate level speaking anxiety. It implies that the students “sometimes” feel anxious using English when they join public speaking class, and based on their anxiety the EFL students have some solutions in speaking anxiety.Keywords: EFL Students, Anxiety, Public Speaking Activity